Spike architecture traits associated with type II resistance to fusarium head blight in bread wheat - Franco, Maria Fiorella (2021)
Fusarium head blight (FHB) remains a devastating disease in bread wheat (Triticum aestivum L.). Genetic resistance to FHB is complex; aside from active physiological resistance, plant developmental and morphological traits indirectly affect disease progression and provide a passive resistance mechanism. Here, the relationship between FHB Type II resistance and spike architecture traits was evaluated in a recombinant inbred line (RIL) population of bread wheat in field experiments during two crop seasons under a completely randomized block design with two replications. Point inoculation was carried out at anthesis of each RIL. Disease severity at 21 days post inoculation (dpi), area under the disease progress curve (AUDPC) comprising severity measurements at 12, 17 and 21 dpi, rachis length, spike density, number of spikelets per spike, number of florets per spike and number of florets per spikelet were determined. The population showed significant variation for all traits. Heritability was moderate-high for FHB severity (0.69) and AUDPC (0.63) and high for spike architecture traits (0.74–0.92). FHB severity at 21 dpi and AUDPC were significantly associated with number of florets per spike [r = 0.38 (P < 0.001) and r = 0.31 (P < 0.01) respectively] and with the number of florets per spikelet [r = 0.28 (P < 0.01) and r = 0.27 (P < 0.05) respectively], reflecting a greater spread of the fungus in spikes with higher floret number. These results suggest that the number of florets per spike and per spikelet should be considered in FHB resistance breeding efforts, because selection of lines with higher number of florets could lead to a correlated selection response towards increased FHB levels under field conditions.